Oral Memoirs of John D. Nettles - Nettles, John D. (My University, 2016)
An oral history interview with John D. Nettles, MD, first chair of the Department of Obstetrics and Gynecology at the Tulsa Medical College.
Keywords: University of Oklahoma. Tulsa Medical College -- History.; Nettles, John D. -- Interviews.; Gynecologists -- Interviews.; Nettles, John D. -- Career in medical education.; Medical education -- Oklahoma -- History.; Medical colleges -- Oklahoma -- History.